Correlation between Interleukin 10 Serum Levels and Severity of Peripheral Neuropathy in Multibacillary Leprosy Patients a Research Article - Fajar Sekti Reliyana; Hexanto Muhartomo; Endang Kustiowati; Yosep Ferdinand Rahmat Sugiyanto; Retnaningsih Retnaningsih; Arinta Puspita Wati; Rahmi Ardhini; Aditya Kurnianto (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
ABSTRACT  Background of the ResearchLeprosy is a chronic infectious peripheral neuropathy caused by Mycobacterium leprae. Clinical presentations of leprosy neuropathy are obtained when the nerve damage is more than 30% of peripheral nerve fibers. The anti-inflammatory property of interleukin 10 is supposed to protect tissue from the damage caused by proinflammatory cytokines. Instead, it causes extensive nerve damage due to suppression of the cellular immune system, failure of forming granuloma to limit the growth of Mycobacterium leprae. As a result, it multiplies and spreads. Purpose of the ResearchThe purpose of the research is to analyze the correlation between interleukin levels 10 serum and the severity of peripheral neuropathy. Methods of the ResearchThe method used is cross-sectional research on 30 subjects with multibacillary leprosy aged 18-65 at the Neurology Department of Kelet Hospital Jepara from September to October 2021. The questionnaire was used to collect data of the patients. Interleukin level 10 serum evaluation is assessed by examining blood serum. Data analysis used Spearman Correlation Test. The significant result occurs if it is p<0.05. Research resultPatients with multibacillary leprosy are mostly men (73.3%). There is also a strong significant correlation between interleukin 10 levels and the severity of peripheral neuropathy (p<0.001) with rho (0.7) ConclusionThere is a strong and significant correlation between serum interleukin 10 levels and the severity of peripheral neuropathy in multibacillary leprosy Keywords: multibacillary leprosy, interleukin 10, peripheral neuropathy